Development of Holistic Face Processing From Childhood and Adolescence to Young Adulthood in Chinese Individuals - Sun, Yini; Li, Qinglan; Cao, Xiaohua (Frontiers in Psychology, 2020)
Previous studies have indicated that holistic face processing is important for the development of face perception. The purpose of this study was to verify the development trajectory of holistic processing, from older childhood to young adulthood, using the complete composite paradigm. Participants from three different age groups (children, adolescents, young adults) were recruited for this study. The results showed that all groups demonstrated the composite effect with similar magnitude. Furthermore, face processing performance improved with age. These results, together with previous results, imply it is a race-general phenomenon that holistic face processing is similar among older children, adolescents, and young adults.